Meningkatkan Motivasi Belajar Peserta Didik Kelas V SDN 05 Enam Lingkung Setelah Kembali Pembelajaran Tatap Muka - Nurdiana, Nurdiana (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
Learning that is usually carried out in educational institutions so far is face-to-face learning before the world is called a global disaster, namely the corona virus. Even in elementary schools, learning is carried out face-to-face between teachers and students. However, when the corona virus also reached Indonesia, the face-to-face learning that was usually carried out turned into learning at home (BDR). More than 2 years of implementing home learning (BDR) has an impact on students. One of them is that they become less motivated to learn. The aims of this study were to (1) describe the learning motivation of students; (2) describe how to increase students' learning motivation. The results of this study are (1) learning motivation is the driving force of individuals both internally and externally to achieve learning objectives (2) how to increase students' learning motivation is to improve the quality of learning, choose appropriate learning methods, maximize learning facilities, utilize the use of media, conduct learning evaluation.